2004
DOI: 10.1007/s00436-003-0992-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity against Toxoplasma gondii in mice induced by a chimeric protein rSAG1/2

Abstract: The aim of this study was to test the protective immunity against Toxoplasma gondii in mice induced by a chimeric protein rSAG1/2. The PCR-amplified SAG2 fragment (558 bp) digested with the restriction enzyme XhoI was inserted into the XhoI site of plasmid pGEX-6p-1, termed pGexSAG2. The PCR-amplified SAG1 fragment (1,008 bp) digested with restriction enzymes EcoRI and XhoI was cloned into the EcoRI/ XhoI sites of a separate plasmid pGEX-6p-1, termed pGexSAG1. The SAG2 fragment (HindIII/HindIII) excised from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 24 publications
0
44
0
1
Order By: Relevance
“…Heretofore, only one study has found that two chimeric antigens, namely, EC2 and EC3, which contain six antigenic regions of the T. gondii MIC2, MIC3, M2AP, dense granule antigen 3 (GRA3), GRA7, and surface antigen 1 (SAG1) proteins, improve the serological diagnosis of toxoplasmosis in adults with an acquired infection and infants born to mothers with a primary T. gondii infection contracted during pregnancy (3). Moreover, owing to the complexity of the parasite life cycle and the variability of the parasite antigens, multiepitope products have become an attractive strategy in the development of vaccines against toxoplasmosis (6,31).…”
mentioning
confidence: 99%
“…Heretofore, only one study has found that two chimeric antigens, namely, EC2 and EC3, which contain six antigenic regions of the T. gondii MIC2, MIC3, M2AP, dense granule antigen 3 (GRA3), GRA7, and surface antigen 1 (SAG1) proteins, improve the serological diagnosis of toxoplasmosis in adults with an acquired infection and infants born to mothers with a primary T. gondii infection contracted during pregnancy (3). Moreover, owing to the complexity of the parasite life cycle and the variability of the parasite antigens, multiepitope products have become an attractive strategy in the development of vaccines against toxoplasmosis (6,31).…”
mentioning
confidence: 99%
“…Among the 57 guinea pigs included in the study, all had a moderate loss of weight (<10% of their body weight) without any clinical symptoms. We found the use of the guinea pig a non-lethal model in this study better suited to determine vaccine efficacy of SAG-1 than the lethal mouse model which is more often used (Petersen et al 1998;Nielsen et al 1999;Chen et al 2002;Fachado et al 2003;Yang et al 2004). Indeed, the principal objective of vaccination for veterinary as well as human use is to prevent congenital infection resulting from an asymptomatic or mildly symptomatic primary infection.…”
Section: Resultsmentioning
confidence: 91%
“…SAG1 gene, SAG2 gene, and a hybrid gene consisting of SAG1 and SAG2 sequences had been, respectively, cloned in our previous work to produce recombinant SAG1 (rSAG1) protein [22,43], recombinant SAG2 (rSAG2) protein [23,43], and a recombinant chimeric protein, rSAG1/2 [24,43]. Further animal studies in mice demonstrated that rSAG1, rSAG2, or rSAG1/2 emulsified with an oil adjuvant, Vet L-10, induced partial protection against a lethal subcutaneous challenge of T. gondii tachyzoites [43]. If alternative effective adjuvants, such as the PLG polymer are used to make these recombinant proteins more immunogenic, more protective immunity against T. gondii may be achieved in animals.…”
Section: Preparation Of Toxoplasma Sag-loaded Microparticlesmentioning
confidence: 99%
“…Previous studies have shown that induction of both lymphocyte proliferation and IFN-γ production (one of Th1-type cytokines) positively correlates with protective Th1 cell-mediated immunity against T. gondii [43,44,51]. In addition, IFN-γ has been demonstrated to be a critical mediator that has to be secreted for as long as possible in order to maintain anti Toxoplasma immunity [52,53].…”
Section: Protective Immunity By Toxoplasma Sag-loaded Microparticlesmentioning
confidence: 99%